Overexpression of plasma membrane Na+/H+ antiporter OsSOS1 gene improves salt tolerance in transgenic rice plants - Awaji, Sushma M; Hanjagi, Prashantkumar S; BN, Pushpa; VR, Sashidhar (ORYZA-An International Journal of Rice, 2021)
Crop productivity is greatly affected by soil salinity; therefore, improvement in salinity tolerance of crops is a major goal in salt-tolerant breeding. The Salt Overly Sensitive (SOS) signal-transduction pathway plays a key role in ion homeostasis and salt tolerance in plants. In plants pumping of Na+ from the root cells is mediated by the plasma membrane Na+/H+ antiporter (SOS1) which plays important role in preventing the accumulation of toxic levels of Na+ in cytosol. In the present study, OsSOS1 (NHX7), gene was overexpressed in rice (var-Vikas) by Agrobacterium mediated In Planta transformation technique. To screen putative T1 plants for salt tolerance, stringent salt screening test was followed and root and shoot growth of transformants were used as selection criterion. Some of the putative transgenics showed significantly higher root growth compared to wild type. To confirm the presence of transgene in putative T1 transgenic plants, PCR based approach was followed using genomic DNA. The result showed that 16 % of the selected seedlings from the stringent salt screening test were PCR positives. Five selected lines were positive for RT-PCR analysis. Physiological studies such as chlorophyll content, membrane permeability, cell viability and sodium /potassium content analysis were alsoconducted to assess their levels of tolerance. Some of the T1 transformants showed lower percent reduction in chlorophyll content and less membrane leakage, higher cell viability and maintained higher K/Na ratio after NaCl treatment compared to wild type. These results clearly demonstrate that transgenic rice plants overexpressing OsSOS1 have better salt-tolerance. This could be attributed to extrusion of excess Na+ from cytosol into the apoplast and thereby reducing the toxic effects of Na+in the cell.